Лексикографічне відтворення колірних назв у мовотворчості Євгена Сверстюка - Козирєва, З. (Лексикографічний бюлетень, 2017)
In the article the words indicating colors are examined as an important part of Yevhen Sverstyuk’s means of expression system. Special attention is paid to the originality of color-related terms and expressions used both in literal and figurative meanings. The use of such lexical tools is strongly determined by the writer’s unique artistic concept along with his peculiar aesthetic principles and world outlook, which is specially noted in the article. In addition, color terms are presented in the form of dictionary entries.